The relationship between smartphone using style and sleep quality and psychiatric symptoms among a foundation university students - Yücel, Emin Erinç; Önen Ünsalver, Barış (The European Research Journal, 2020)
Objectives: We aimed to measure problematic smartphone use frequency and it’s association with sleep problems and psychiatric symptoms in a sample of university students.Methods: The data in the study was collected by using a sociodemographic data form, the Smartphone Addiction Scale (SAS), the Pittsburgh Sleep Quality Index (PSQI), the Epworth Sleepiness Scale (ESS) and the Brief Symptom Inventory (BSI).Results: Based on the SAS median score, the participants were divided into two groups as the low-level smartphone use (SAS score < 79) and the high-level smartphone use (SAS score > 79) groups. In the high-level smartphone use group, general sleep quality was lower, sleep latency was longer, scores of sleep disorder and daytime dysfunction were higher as measured by PSQI and the BSI scores were higher (p < 0.001). As a result of the study, it was observed that, as smartphone use increased and became problematic, sleep quality decreased, and daytime dysfunction and psychiatric symptoms increased. SAS scores were positively correlated with both PSQI and ESS scores. SAS score was found as a predictor of PSQI scores in the regression analysis. Conclusions: This study shows that the relationship between problematic smartphone use and decreased sleep quality and increased psychiatric symptomatology in university students is still an important public health issue. Responsible and mindfull use of smartphones by the students throughout the day may provide a positive effect on their sleep.